PERBEDAAN PENGETAHUAN MAHASISWA TENTANG HIV/AIDS YANG DIBERI METODE BELAJAR MULTIMEDIA DAN CERAMAH PLUS - Maria Rantung (Jurnal Ilmiah Perawat Manado (Juiperdo), 2012)
Some studies show that multimedia can improve knowledge. The purpose of thisstudy was to determine the level of knowledge about HIV/AIDS throughmultimedia and lecture methods plus. The study design was quasi-experimental, while the sampling method with purposive sampling. The total sample of 50 respondents from the Ministry of Health polytechnic student of midwifery Manado consisting of 2 groups: a multimedia learning with 25 respondents and group learning with lectures plus 25 respondents. Data analysis was performed using the t test. The results showed that the method of multimedia experience average increase in knowledge about HIV/AIDS was 7.04 with SD 3.38, while lectures plus increased an average of 3.48 with SD 1.82. Mean difference between both methods was of 3.56 with 95% CI (2.01 to 5.10) and p = 0.00 (? <0,05). Conclusion that there is an increase in knowledge through education with multimedia and lecture method but more effective methods of multimedia to enhance the students' knowledge of HIV/AIDS.